2015
DOI: 10.1007/s10802-015-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Parent-Report Mood and Feelings Questionnaire (MFQ) in an Outpatient Mental Health Sample

Abstract: The current investigation examined the internal structure and discriminant validity of the parent-report Mood and Feelings Questionnaire (MFQ-P), a commonly used measure of depressive symptoms in youth. A total of 1493 families with youth ages 5 to 18 (61.02 % male) presenting for treatment at an outpatient mental health clinic were randomly allocated to an Exploratory Sample 1 or to a Replication Sample 2. Internal structure of the MFQ-P was examined using exploratory factor analysis in Sample 1 (N = 769) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 44 publications
8
16
0
Order By: Relevance
“…The Moods and Feelings Questionnaire short version (MFQ, Angold, Costello, Messer, Pickles, Winder & Silver 1995;Messer, Angold, Costello, Loeber, Van Kammen & Stouthamer-Loeber, 1995) was used to determine how participants were feeling in the past two weeks. Previous studies have found it to be a reliable and valid measure of depression in populations aged 6-17 years (e.g., Jeffreys et al, 2016).…”
Section: Survey Instrumentsmentioning
confidence: 99%
“…The Moods and Feelings Questionnaire short version (MFQ, Angold, Costello, Messer, Pickles, Winder & Silver 1995;Messer, Angold, Costello, Loeber, Van Kammen & Stouthamer-Loeber, 1995) was used to determine how participants were feeling in the past two weeks. Previous studies have found it to be a reliable and valid measure of depression in populations aged 6-17 years (e.g., Jeffreys et al, 2016).…”
Section: Survey Instrumentsmentioning
confidence: 99%
“…Although MDD is conceptualized as an internalizing disorder, the caregiver's version helps to capture the construct of depression more comprehensively and seems to better predict a depressive episode when compared to the adolescent report in isolation. 8,14 The present study, however, is not without limitations: the sample for the cognitive debriefing step was very small and, despite trying to cover different ages and genders, we did not control for socioeconomic status or diagnostic categories. Also, the fact that all subjects were patients at mental health clinics limits the generalizability of findings to community settings.…”
Section: Discussionmentioning
confidence: 93%
“…The MFQ is one of the most frequently used instruments to assess depressive symptoms in children and adolescents in the international literature. 12,14 The absence of a Brazilian Portuguese translation of its long version prevents its use in a country currently with a population of 63 million children and adolescents. 15 We has been applied with the objective of verifying its psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a mood assessment would occur before undergoing psychoacoustic stimulation. The mood assessment was based on a pre-existing model of an already established Mood and Feelings Questionnaire (MFQ) [27,28]. Moreover, mood assessments took place from the initial session, at the halfway point and on the concluding session: sessions 1, 4 and 8, respectively.…”
Section: Methodsmentioning
confidence: 99%